Pengaruh Kualitas Produk dan Eksklusivitas Produk terhadap Keputusan Pembelian Konsumen: Studi pada Followers Instagram Faith Industries - Moch Shiddiq Hermaya Putra; Umi Narimawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of social media, particularly Instagram, has changed the marketing strategies of the fashion industry by placing visuals as the main means of shaping perceptions and purchasing decisions. The high intensity of digital displays is not always accompanied by consistent product quality, which has the potential to affect consumer trust. This study aims to analyze the influence of product quality and product exclusivity on purchasing decisions among Instagram followers of Faith Industries. The approach used is quantitative with an associative and verifiable design. Data was collected through an online questionnaire administered to 96 respondents selected using purposive sampling. The analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination using SPSS. The results showed that product quality had a positive and significant effect on purchasing decisions, while product exclusivity had no significant partial effect. Simultaneously, both variables had a significant effect with a contribution of 30.7%.